2016
DOI: 10.1080/15384101.2016.1138185
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for the deubiquitinase USP1 in the control of centrosome duplication

Abstract: Defects in the regulation of centrosome duplication lead to tumorigenesis through abnormal cell division and resulting chromosome missegregation. Therefore, maintenance of accurate centrosome number is critical for cell fate. The deubiquitinating enzyme USP1 plays important roles in DNA repair and cell differentiation. Importantly, increased levels of USP1 are detected in certain types of human cancer, but little is known about the significance of USP1 overexpression in cancer development. Here we show that Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…We showed that USP9X, through stabilizing CEP131, regulates centrosome duplication and mitotic fidelity. In addition to our study, numerous reports showed the involvement of deubiquitination enzymes including BAP1, USP33, USP1, USP44, CYLD and USP21 in centrosome regulation and chromosomal stability365354555657, supporting a notion that deubiquitinases are the key regulators in centrosome homeostasis and genome stability.…”
Section: Discussionsupporting
confidence: 88%
“…We showed that USP9X, through stabilizing CEP131, regulates centrosome duplication and mitotic fidelity. In addition to our study, numerous reports showed the involvement of deubiquitination enzymes including BAP1, USP33, USP1, USP44, CYLD and USP21 in centrosome regulation and chromosomal stability365354555657, supporting a notion that deubiquitinases are the key regulators in centrosome homeostasis and genome stability.…”
Section: Discussionsupporting
confidence: 88%
“…We showed that USP9X is spatially restricted to the centrosome by PCM1 and CEP55 and regulates centrosome duplication in its catalytic activity-dependent manner, although it remains to be explored whether and how PCM1 or CEP55 contributes to USP9X-promoted centrosome biogenesis in the future. In addition to our finding, several studies reported that the deubiquitination enzymes including BAP1, USP33, USP1, USP44, cylindromatosis (CYLD), and USP21 have been implicated in centrosome regulation (43)(44)(45)(46)(47)(48), pointing to a role of deubiquitinases as key regulators in centrosome homeostasis. Possibly, PCM1 and/or CEP55 could be controlled by these enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…UAF1 constitutively binds to USP1, USP12, and USP46, and this binding greatly enhances their deubiquitinase activity. The UAF1/USP1 complex deubiquitinates a wide range of substrates and has been implicated in the regulation of DNA repair processes [15][16][17][18] , tumor pathogenesis [19][20][21][22][23] , and antiviral innate immunity 24 . USP1 can deubiquitinate and stabilize inhibitors of DNA binding proteins (IDs) and subsequently promote the maintenance of mesenchymal stem cells in osteosarcoma 6,15 .…”
mentioning
confidence: 99%